1988
DOI: 10.1002/bip.360270302
|View full text |Cite
|
Sign up to set email alerts
|

Structural versatility of peptides from Cα,α‐dialkylated glycines. I. A conformational energy computation and x‐ray diffraction study of homo‐peptides from Cα,α‐diethylglycine

Abstract: Conformational energy computations on a derivative and a homo‐dipeptide of Cα,α‐diethylglycine were performed. In both cases the N‐ and C‐terminal groups are blocked as acetamido and methylamido moieties, respectively. It was found that the Cα,α‐diethylglycine residues are conformationally restricted and that the minimum energy conformation corresponds to the fully extended C5 structure when the NCαC′ bond angle is smaller than 108° (as experimentally observed). The results of the theoretical analysis are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 35 publications
4
78
0
Order By: Relevance
“…4). [12][13][14] The extended C 5 -conformation is an extended planar conformation of the peptide-backbone, showing two torsion angles of fϭ180°, jϭ180°. Achiral homopeptides composed of dipropylglycine, dibutylglycine, or diphenylglycine also preferentially form the extended conformation.…”
Section: Secondary Structures Of Peptides Composed Of a Aa Adisubstimentioning
confidence: 99%
“…4). [12][13][14] The extended C 5 -conformation is an extended planar conformation of the peptide-backbone, showing two torsion angles of fϭ180°, jϭ180°. Achiral homopeptides composed of dipropylglycine, dibutylglycine, or diphenylglycine also preferentially form the extended conformation.…”
Section: Secondary Structures Of Peptides Composed Of a Aa Adisubstimentioning
confidence: 99%
“…"-dialkylated residues with linear substituents, like Ca~a-dimethylglycine or a-aminoisobutyric acid (Aib) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), Capa-diethylglycine (Deg) (5,10,17), and Ca9-di-n-propylglycine (Dpg) (5,10,18), relatively few studies have been reported on peptides containing l-aminocycloalkane-I-carboxylic acids (Accn, where n is the number of carbon atoms in the cycloalkane ring). Recent X-ray diffraction investigations in our laboratory suggest that both l-aminocyclohexane-1-carboxylic acid (Acc6) (19)(20)(21)(22) and l-aminocyclopentane-I-carboxylic acid (Acc5), earlier referred to as cycloleucine and abbreviated as Cle, Cyl, cycloLeu or cLeu (23) strongly prefer folded backbone conformations in the 310/ahelical region of the conformational space (@ = k 6 0 f 20°, $ = k 30" 2 20") (24).…”
Section: Introductionmentioning
confidence: 99%
“…While the two major allowed conformational areas were associated with either right-or left-handed helical conformations (both a and 310), the calculation also revealed other sets of energetically feasible values for 4 and q, adjacent to the a,a-dialkyl residue associated with extended structures as well as turns. The effect on conformation of alkyl groups larger than methyl as substituents in a,a-dialkyl amino acids has also been investigated (11,12). Despite the variety of conformations theoretically available to a,a-dialkyl amino acids, the impact of multiple substitutions ofthis type of amino acid on the overall conformation of a peptide is dramatic.…”
Section: Introductionmentioning
confidence: 99%